PROFIL KANDIDOSIS INTERTRIGINOSA DI POLIKLINIK KULIT DAN KELAMIN BLU RSUP PROF. DR. R. D. KANDOU MANADO PERIODE JANUARI – DESEMBER 2012 - Wowor, Samuel Rian; Pandaleke, Herry E. J.; Kapantow, Marlyn Grace (Universitas Sam Ratulangi, 2014)
Abstract: Intertriginous Candidosis is a superficial mycoses affecting skin folds caused by yeast of the genus Candida, mostly Candida albicans. The purpose of this study was to evaluate the profile of intertriginous candidosis in Dermatovenereology clinic of Prof. Dr. R. D. Kandou Hospital Manado during the period from January – December 2012. This study was conducted retrospectively on medical records of new patients diagnosed with intertriginous candidosis in Dermatovenereology clinic of Prof. Dr. R. D. Kandou Hospital Manado during the period from January – December 2012. The result of this study showed that there were 37 patients (3.37%) with intertriginous candidosis among 1096 new patients, significantly higher in female (64.86%) than in male patients, highest rate recorded was within 45-64 age group (45.95%), most skin fold affected was groin (16.22%), and the most commonly used therapy was a combination of topical antifungal and oral antihistamine (29.74%). Keywords: superficial mycoses, intertriginous candidosis, retrospective study Abstrak: Kandidosis Intertriginosa merupakan mikosis superfisialis yang terkena pada daerah lipatan kulit yang disebabkan oleh jamur dari genus Candida umumnya Candida albicans. Tujuan penelitian ini adalah untuk mengetahui profil kandidosis intertriginosa di poliklinik Kulit dan Kelamin RSUP Prof. Dr. R. D. Kandou Manado periode Januari – Desember 2012. Penelitian ini dilakukan secara retrospektif dari rekam medik pasien baru dengan diagnosis kandidosis intertriginosa di Poliklinik Kulit dan Kelamin RSUP Prof. Dr. R. D. Kandou Manado periode Januari – Desember 2012. Hasil penelitian ini menunjukkan bahwa ada 37 pasien (3,37%) kandidosis intertriginosa dari 1096 pasien baru, lebih banyak ditemukan pada perempuan dibanding laki-laki, kelompok umur terbanyak pada 45-64 tahun, lokasi lipatan kulit paling banyak terkena pada lipat paha, dan terapi yang paling banyak digunakan adalah antifungi topikal dan antihistamin. Kata Kunci: mikosis superfisialis, kandidosis intertriginosa, penelitian retrospektif